Study of the Causes of Change Orders in Infrastructure Work Implementation and its Impact on Project Performance - Moh. Sholahuddin; Ichwan Hadi Saputra (Universitas Islam Raden Rahmat, Malang, 2025)
Infrastructure work often undergoes changes during the construction phase to adapt to field conditions that differ from the initial planning. These changes may involve adding work volume, modifying technical specifications, or adjusting work schedules due to field conditions, policy changes, or other external factors. If not managed properly, these changes can lead to cost overruns, project delays, and even disputes among the parties involved. This research aims to identify the factors causing changes in orders and their impact on project performance. The method used is the distribution of questionnaires to involved contractors, followed by data analysis using the Relative Importance Index (RII) approach. The results show that there are 7 main factors, namely Planning and Design, Natural Factors, Owners, Construction, External Causes, Administration, and Policy Changes, with 40 indicators causing changes in orders in infrastructure projects. Additionally, it was found that changes in orders impact project performance in terms of cost, quality, and time, with 15 indicators representing those impacts. This finding makes an important contribution to project management practices, particularly in efforts to control changes in work during construction execution. The results of this research can serve as a basis for consideration in planning, monitoring, and decision-making to minimize the risks of work changes and improve overall project performance.